(untitled) (Journal of Partial Differential Equations, 2012)
In this paper we mainly study the relation between |A|^2, |H|^2 and cosα (α is the Kähler angle) of the blow up flow around the type II singularities of a symplectic mean curvature flow. We also study similar property of an almost calibrated Lagrangian mean curvature flow. We show the nonexistence of type II blow-up flows for a symplectic mean curvature flow satisfying |A|^2≤λ|H|^2 and cosα≥δ>1-12λ(½≤α≤ 2), or for an almost calibrated Lagrangian mean curvature flow satisfying |A|^2≤λ|H|^2 and cosθ≥δ>max 0,1-1λ (34≤λ≤ 2), where θ is the Lagrangian angle.